2013
DOI: 10.1038/labinvest.2012.154
|View full text |Cite
|
Sign up to set email alerts
|

SOCS-3 is downregulated in progressive CKD patients and regulates proliferation in human renal proximal tubule cells in a STAT1/3 independent manner

Abstract: Proliferation and the sequence of epithelial to mesenchymal transition (EMT) and mesenchymal to epithelial transition (MET), called epithelial-mesenchymal-epithelial (EME) cycling are pivotal mechanisms of kidney repair and fibrosis. Furthermore, data suggest that dedifferentiation (EMT) is a prerequisite for proliferation of tubule cells. These processes have been shown to be regulated by STAT1/3 signaling. Suppressor of cytokine signaling-3 (SOCS-3) is a negative regulator of STAT1/3 signaling. Using a trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
(86 reference statements)
0
9
0
Order By: Relevance
“…Importantly, Fujitake et al ( 33 ) reported aberrant expression of SOCS1 in patients with colorectal cancer. A previous study also demonstrated that EMT is regulated by STAT1/3 signaling, while SOCS is a negative regulator of STAT1/3 signaling ( 34 ). Thus, EMT may be negatively regulated by SOCS, which was in accordance with the present study, whereby the expression of E-cadherin decreased significantly and the expression levels of N-cadherin, vimentin and Snail increased significantly in si-SOCS + miR-885-5p inhibitor groups compared with the miR-885-5p inhibitor group alone.…”
Section: Discussionmentioning
confidence: 84%
“…Importantly, Fujitake et al ( 33 ) reported aberrant expression of SOCS1 in patients with colorectal cancer. A previous study also demonstrated that EMT is regulated by STAT1/3 signaling, while SOCS is a negative regulator of STAT1/3 signaling ( 34 ). Thus, EMT may be negatively regulated by SOCS, which was in accordance with the present study, whereby the expression of E-cadherin decreased significantly and the expression levels of N-cadherin, vimentin and Snail increased significantly in si-SOCS + miR-885-5p inhibitor groups compared with the miR-885-5p inhibitor group alone.…”
Section: Discussionmentioning
confidence: 84%
“…The critical role of SOCS3 is manifested by its binding to both JAKs and cytokine receptors, which results in the inhibition of STAT3 phosphorylation. STAT3 triggers a variety of gene expressions in response to cytokine (such as IL-6 and IL-10) and growth factor stimulation and plays a critical role in many cellular biological processes involved in anti-/proinflammatory responses, cell growth, and cell death [27,28]. However, we demonstrated that early EV71 infection quickly activated SOCS protein expression and inhibited IFN-induced STAT3 phosphorylation.…”
Section: Discussionmentioning
confidence: 66%
“…10,11,13 In particular, SOCS1/3 expression pattern is altered in inflammatory diseases 12,18,27,28 and correlates with cardiovascular risk and progressive loss of renal function in CKD. 29,30 Our reports in diabetic patients and animals 17,31 proposed SOCS1 induction as a compensatory mechanism not sufficient to suppress JAK/STAToveractivation in renal disease. Accordingly, SOCS1 gene therapy using local and systemic delivery routes mitigates proteinuria, renal inflammation, and fibrosis in diabetic mice.…”
Section: Discussionmentioning
confidence: 94%